Kuby Immunology - Goldsby, Richard A. (W.H. Freeman and company, 2000)
Amherst College, MA. Immunology textbook for students. Previous edition, c1997, was titled Immunology, by Janis Kuby. Presents a current and comprehensive introduction to the principles and research in the field. Color highlighting and illustrations. DNLM: Immune System--immunology.